Pengaruh Jumlah Kendaraan Bermotor, Penerimaan Pajak, dan Pertumbuhan Ekonomi terhadap Penerimaan Pajak Kendaraan Bermotor - Ismi Nur Kholifah; Hilda Kumala Wulandari; Dumadi; Indah Dewi Mulyani; Slamet Bambang Riono (Universitas Muhadi Setiabudi, 2020)
This study aims to measure the performance of a bank in terms of risk, income, and capital in Conventional Banks in Indonesia. The data in this study used a sample of 42 conventional banks in Indonesia from 2017 to 2019. Nonperfoming financing is to measure the quality of an asset, credit risk (financing), liquidity risk is promulgated by the Financing to Deposit Ratio, and the size of a company is measured using total assets. Return On Equity and Net Interest Margin are used to measure efficiency analysis. While capital is measured using capital adequacy, The financial statement data used in this study consisted of ROE, FDR, NPF, BOPO, CAR, NOM and Bank Size. The data in this study shows a relationship with the indicators of a financial profitability ratio in conventional banks. Based on an analysis and interpretation of the data that has been carried out, it can be concluded that only one ratio, namely the size of the bank, has a positive influence on ROE, while the financing to deposit ratio, nonperfoming financing, operational costs, capital adequacy ratio, net interest margin does not have a significant effect on ROE in conventional banks.